Pengembangan Lembar Kerja Peserta Didik (LKPD) Berpola Claim, Data, Warrant (Cdw) untuk Meningkatkan Kemampuan Argumentasi Siswa - Rahayu Rahayu; Muhammad Haris Effendi (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2020)
This study aims to develop student worksheets (LKPD) patterned claim, data, warrant (CDW) on human respiratory system material and find out how teachers respond and student responses and the effect of using LKPD on student argumentation ability. The development model used in this research is addie development model consisting of 5 stages, namely analysis, planning, development, implementation and evaluation. The development of this LKPD uses due diligence based on expert validation of materials and validation of media experts, as well as teacher response and student response. Data analysis techniques used are qualitative and quantitative data analysis. The results of both validators state that LKPD is worthy of testing. Furthermore, the results of the teacher's response also stated that the LKPD is feasible in the trial with a score of 93%. Then the results of the odd and even group student response were obtained from kappa test of 0.673 with high category and correlation test of 0.806 with very strong category. This means that the two groups of students have been in touch and agreed to state that LKPD is worthy of trial. In conclusion, students can understand the problem of claims, data, warrant (CDW) arguments judging by the score of the paired sample t test of 0.000 which means that there is an influence of the use of student worksheets (LKPD) on students' argumentation ability. Keywords: Claim, Data, Warrant (CDW), Student Worksheet (LKPD), Argumentation Ability.